Intravitreal Bevacizumab (Avastin) for Diabetic Retinopathy: The 2010 GLADAOF Lecture. (30th March 2011) - Arevalo, J. Fernando; Sanchez, Juan G.; Lasave, Andres F.; Wu, Lihteh; Maia, Mauricio; Bonafonte, Sergio; Brito, Miguel; Alezzandrini, Arturo A.; Restrepo, Natalia; Berrocal, Maria H.; Saravia, Mario; Farah, Michel Eid; et al.
Abstract : This paper demonstrates multiple benefits of intravitreal bevacizumab (IVB) on diabetic retinopathy (DR) including diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR) at 24 months of followup. This is a retrospective multicenter interventional comparative case series of intravitreal injections of 1.25 or 2.5 mg of bevacizumab for DME, PDR without tractional retinal detachment (TRD), and patients who experienced the development or progression of TRD after an intravitreal injection of 1.25 or 2.5 mg of bevacizumab before vitrectomy for the management of PDR. The results indicate that IVB injections may have a beneficial effect on macular thickness and visual acuity (VA) in diffuse DME. Therefore, in the future this new therapy could complement focal/grid laser photocoagulation in DME. In PDR, this new option could be an adjuvant agent to panretina photocoagulation so that more selective therapy may be applied. Finally, TRD in PDR may occur or progress after IVB used as an adjuvant to vitrectomy. Surgery should be performed 4 days after IVB. Most patients had poorly controlled diabetes mellitus associated with elevated HbA1c, insulin administration, PDR refractory to panretinal photocoagulation, and longer time between IVB and vitrectomy.